A multi-component polyoxometalate and its catalytic performance for CO2 cycloaddition reactions1. Issue 22 (14th June 2015) - Chen, Shumin; Liu, Ying; Guo, Jipeng; Li, Pengzhen; Huo, Zhiyuan; Ma, Pengtao; Niu, Jingyang; Wang, Jingping
<x xml:space="preserve">Abstract</x> A multi-component polyoxometalate based on earth-abundant elements (NH4)10[Co8(H2O)10V10Mo23O104(OH)6]·34.5H2O was obtained, which can prompt the coupling of CO2 with epoxides.